Investigation of artificial tooth morphology using a holographic interferometry technique - Apsari, Retna; Bidin, Noriah; Suhariningsih, -; Yoseph, G.Y.; Darmanto, Win; Hartati, Sri; Yuliati, Anita; Harun, Sulaiman Wadi (INOE, 2011)
A surface morphology of artificial tooth is investigated using a holographic interferometry, whereby a virtual three dimensional image is captured on hologram film using a 633nm He-Ne laser. Image of artificial tooth morphology is produced by using optical reconstruction from virtual image, and then captured by a digital camera. It is found that the optimum angle for capturing the virtual image is 90° and it is not possible to produce high quality images using a camera with resolution of 5 megapixels. With the use of a high resolution camera of 10 megapixels, a clear image is captured with sufficient intensity for the interference fringe. This shows that a holographic interferometry technique can be used in conjunction with a 10 megapixel camera for dental imaging in obtaining tooth morphology documentation.